Um novo modelo murino de infecção entérica por Shigella flexneri e teste vacinal de cepa de S. flexneri atenuada - Medeiros, Pedro Henrique Quintela Soares de (2019)
Background:The absence ofa robust pre-clinical model of S. flexneri infectionsis major barrier for the vaccine development for these infections. Objective: To develop an infection model of S.flexneriin antibiotic pre-treated mice which could mimic clinical outcomes and enable investigating the role of micronutrient zinc deficiency (ZD) and evaluation of vaccines. Material and Methods:C57/BL6 mice were fed nourished (ND) or ZD diets and treated with antimicrobials (colistin, gentamycin, metronidazole and vancomycin) for three days prior to oral inoculation with S. flexneri2457T strain 108 CFU/mouse. Diarrhea and bodyweight were observed daily and fecal samples and intestinal tissues were collected for molecular detection of S. flexneriand measurement of inflammatory biomarkers and cytokines by immunoenzymatic assays. Urine and fecal samples were collected for metabolomics analysis by gas nuclear magnetic resonance and microbiome analysis by sequencing of 16S RNAr, respectively. An attenuated S. flexneristrain (with deletion of genes guaBA, sen and set) was tested intranasallyas vaccine candidate for efficacy and immunogenicity.Results: ND mice pretreated with antimicrobials showed S. flexnerifecal excretion for at least a week, while there was no detectionin mice that did not receive antimicrobials. S. flexneriinfection caused diarrhea, weight loss and increased intestinal inflammation between days 2-4 post-infection (pi). These outcomes were dependent on the type 3 secretion system, preferential colonization to the colon with intra and extracellular localization, epithelial disruption, cytokines production (TNF-, IL-1 e IL-10), and modulation of bacterial genera (increased Turicibacter spp. andEubacterium spp.; and decreasedBlautiaspp). Infection in ZD antibiotic pre-trated mice led topersistent colonization for at least 50 days pi and delayed weight loss, diarrhea and intestinal inflammation in comparison with DN mice, as well as extracellular localization of S. flexneri with biofilm-like structures. Metabolomics analysis showed that defects on fatty acid -oxidation, taurine metabolism and degradation of tryptophan are associated with infection in ZD. Pre-vaccinated ND micedid not present weight loss or diarrhea and had shorter courses of pathogen colonization and presented S. flexnerispecific antibody responses. Conclusion:We present a new murine model of shigellosis, which mimics common clinical outcomes in children. ZD promotes persistent colonization, biofilm formation and metabolic alterations in the response to infection. An attenuated strain of S. flexneriwas efficacious and immunogenic in ND mice.